Practicing a Culturally Responsive Feminist Pedagogy in Higher Education: An Examination of a Feminist Classroom from the Perspective of Transformative Learning - Mitsunori Misawa; Juanita Johnson-Bailey (Adult Education Research Conference, 2019)
The purpose of our presentation is to explore how non-White professors, an Asian male pre-tenured professor and a Black female tenured full professor, negotiated their power in their feminist classroom.
Keywords: feminist pedagogy; higher education; race; gender; power dyanmics